2015
DOI: 10.1007/s12253-015-9979-7
|View full text |Cite|
|
Sign up to set email alerts
|

Up-Regulation of miR-21 Expression Predicate Advanced Clinicopathological Features and Poor Prognosis in Patients with Non-Small Cell Lung Cancer

Abstract: MicroRNAs (miRNAs) are endogenous small (19-24 nt long) noncoding RNAs that regulate gene expression in a sequence specific manner. An increasing association between miRNA and cancer has been recently reported. Lung cancer is globally responsible for 1.4 million deaths annually and is the leading cause of cancer-related deaths in both women and men. In this study, we investigated the miR-21 expression in non-small cell lung cancer (NSCLC) to evaluate their value in prognosis of this tumor. Here, we assess miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…The patients with high miR-21 expression had a higher tumor grade and were at higher risk of lymph node metastasis. 21 Over-expressing miR-21 in lung cancer cells could be released into circulation, leading to increased miR-21 levels in blood. 22 Shen et al investigated miRNA profiles in paired lung tumor tissues and plasma specimens from NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The patients with high miR-21 expression had a higher tumor grade and were at higher risk of lymph node metastasis. 21 Over-expressing miR-21 in lung cancer cells could be released into circulation, leading to increased miR-21 levels in blood. 22 Shen et al investigated miRNA profiles in paired lung tumor tissues and plasma specimens from NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is also expressed in blood and hematopoietic cells, which, as mentioned, are sensitive to radiation, explaining the fall in circulating levels of this miRNA after 15 Gy whole thorax irradiation. MiR-21-5p is a well-known lung injury marker303132. But studies with changes in miR-21-5p after radiation have been limited to lung cancer cells2333 and not in irradiated lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Tian et al . showed that altered miR-21 expression is related to NSCLC occurrence, development, and survival analysis indicated that miR-21 expression is negatively correlated with NSCLC progression [33]. MiR-21 is also an important miRNA regulating radiosensitivity of human cancer cells [34, 35].…”
Section: Discussionmentioning
confidence: 99%